STRATEGI PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM) KERUPUK KULIT KOTA PEKANBARU - nofrizal nofrizal (Universitas Lancang Kuning, 2017)
Abstract: This research aim to identify from exsternal and internal factor-factor small and medium enterprises (SMEs)of Kerupuk kulit Kelurahan Sidomulyo Barat Kecamatan Tampan Pekanbaru along with formulation and strategies planning development enterprises in effort to get business connection, broading and increase value profitability for small and medium enterprises (SMEs) of Kerupuk kulit. In this research used metodelogy to made planning and development this enterprises is use analysis Matrik SWOT, and Matrik TWOS. Result from this research showed development strategy can use to Small and Medium Enterprises (SMEs) is stabilitaion Strategy.Keywords:Development Strategy, SWOT, SPACE, TWOS